Biochar in substrate composition for production of teak seedlings - Rezende, Fabiana Abreu; Santos, Victor Alexandre Hardt Ferreira dos; Maia, Claudia Maria Branco de Freitas; Morales, Marina Moura (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the development and quality of clonal seedlings of teak (Tectona grandis) grown in substrate with two types of biochar. The assay was carried out in a randomized complete block design, with ten treatments and four replicates: CS, commercial substrate, composed of pine bark and vermiculite at a ratio of 4:1; NS, nursery substrate composed of carbonized rice husk and coconut fiber at 1:1; and the remaining treatments were composed of the inclusions of biochar (BC) or activated biochar (BCA) in the CS, at the proportions of 25, 50, 75, and 100%. The development and quality parameters of seedlings were evaluated 90 days after striking the minicuttings in the substrates. BCA substrate additions at 25, 50, and 100% allowed for a development of height and stem diameter comparable to that of the NS. Biochar without the activation procedure does not improve quality parameters of seedlings, in comparison with the commercial substrate. The use of 25% activated biochar added to the commercial substrate is enough to improve seedling growth performance to the same level as that provided by the already validated NS.